Konstruksi Otoritarianisme Hukum Islam Menurut Khaled M. Abou El-Fadl - Ridwan, Mohammad (LP2M IAIN Samarinda, 2017)
Quran was sent down for the humanity, its consequently guiding to drive justice, dignity and a mercy of the universe. This paper tried to discribe of the triangle of text, reader and author in islamic legal opinion. The cource strictly to differ where are authoritative and authoritarian in the same time. Here is Khaled Khaled as a prominent moslem thinker standing consistantlyÂ in front line againts wahabism on its fatawa or islamic legal opinions. Khaled offers methodology of how to interpret of the meaning of the law texts, it is hermeneutic. The characteristics of this kind of methodology is that there is closed relation to the author, text, context, and interpreting of reader. So, the meaning of Islamic law texts can be classified into two categories, authoritarianism and authoritative meaning.